Brain Gym : senam otak / Paul E. Dennison, Gail E. Dennison ; editor, A. Ariobimo Nusantara ; alih bahasa, Ruslan, Rahaju Morris - DENNISON, Paul E.; Morris, Rahayu; Ruslan; Nusantara, A. Ariobimo; Dennison, Gail E. (Grasindo, 2006)
78 hlm. ; 27 cm.